Morphological configuration of the cranial base among children aged 8 to 12 years (2016)
Background: Cranial base is used as reference structure to determine the skeletal type in cephalometric analysis. The purpose was to assess the cranial base length on lateral cephalic radiographs of children between 8 and 12 and compare these measurements with baseline studies in order to evaluate the relationship between the length and the cranial base angle, articular angle, gonial angle and skeletal type. Methods: A Cross-sectional study in 149 children aged 8-12 years, originally from Aburrá Valley, who had lateral cephalic radiographs and consented to participate in this study. The variables studied included: age, sex, sella-nasion, sella-nasion-articular, sella-nasion-basion, articular-gonion-menton, gonion-menton, sella-nasion-point B, sella-nasion-point A y point A-nasion-point B. These variables were digitally measured through i-dixel 2 digital software. One-way ANOVA was used to determine mean values and mean value differences. The values obtained were compared with previous studies. A p value <0.05 was considered significant. Results: Cranial base lengths are smaller in each age and sex group, with differences exceeding 10 mm for measurement, compared both with the study by Riolo (Michigan) and the study carried out in Damasco (Antioquia). No relation was found between the skeletal type and the anterior cranial base length, the sella angle and the cranial base angle. Also, no relation was found between the gonial angle and sella angle or the cranial base angle. Conclusion: The cranial base varies from one population to another. Accordingly, compared to other studies it is shorter for the assessed sample. © 2016 The Author(s).